Helminth coinfection does not affect therapeutic effect of a DNA vaccine in mice harboring tuberculosis. - Fabiani G Frantz; Rogério S Rosada; Camila Peres-Buzalaf; Franciele R T Perusso; Vanderlei Rodrigues; Simone G Ramos; Steven L Kunkel; Célio L Silva; Lúcia H Faccioli (Public Library of Science (PLoS), 2010)
BACKGROUND: Helminthiasis and tuberculosis (TB) coincide geographically and there is much interest in exploring how concurrent worm infections might alter immune responses against bacilli and might necessitate altered therapeutic approaches. A DNA vaccine that codifies heat shock protein Hsp65 from M. leprae (DNAhsp65) has been used in therapy during experimental tuberculosis. This study focused on the impact of the co-existence of worms and TB on the therapeutic effects of DNAhsp65. METHODOLOGY/PRINCIPAL FINDINGS: Mice were infected with Toxocara canis or with Schistosoma mansoni, followed by coinfection with M. tuberculosis and treatment with DNAhsp65. While T. canis infection did not increase vulnerability to pulmonary TB, S. mansoni enhanced susceptibility to TB as shown by higher numbers of bacteria in the lungs and spleen, which was associated with an increase in Th2 and regulatory cytokines. However, in coinfected mice, the therapeutic effect of DNAhsp65 was not abrogated, as indicated by colony forming units and analysis of histopathological changes. In vitro studies indicated that Hsp65-specific IFN-gamma production was correlated with vaccine-induced protection in coinfected mice. Moreover, in S. mansoni-coinfected mice, DNA treatment inhibited in vivo TGF-beta and IL-10 production, which could be associated with long-term protection. CONCLUSIONS/SIGNIFICANCE: We have demonstrated that the therapeutic effects of DNAhsp65 in experimental TB infection are persistent in the presence of an unrelated Th2 immune response induced by helminth infections.